2020
DOI: 10.1039/d0dt00092b
|View full text |Cite
|
Sign up to set email alerts
|

Effect of positional isomers on the photochromic behaviors of bipyridyltriazolium chloroantimonate hybrids

Abstract: Two chloroantimonates with isomeric bipyridyltriazoliums exhibit distinct photochromic behaviors, of which 1 is the first reported photochromic chloroantimonate hybrid.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 53 publications
0
5
0
Order By: Relevance
“…[34][35][36][37][38] Exploring lead-free low-dimensional OIMH a Advanced Research Institute of Multidisciplinary Science, School of Materials materials has been proposed by replacing lead with other metals, such as Sn, Cu, Sb etc., 29,39,40 which are hopeful to improve both the structural stability and the PLQY of OIMHs. 39,41,42 In addition, self-trapped excitons (STEs) usually formed in low-dimensional OIMHs, which could generate broadband emission even covering the entire visible spectrum. 43 Therefore, it is particularly important to develop lead-free low-dimensional OIMHs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[34][35][36][37][38] Exploring lead-free low-dimensional OIMH a Advanced Research Institute of Multidisciplinary Science, School of Materials materials has been proposed by replacing lead with other metals, such as Sn, Cu, Sb etc., 29,39,40 which are hopeful to improve both the structural stability and the PLQY of OIMHs. 39,41,42 In addition, self-trapped excitons (STEs) usually formed in low-dimensional OIMHs, which could generate broadband emission even covering the entire visible spectrum. 43 Therefore, it is particularly important to develop lead-free low-dimensional OIMHs.…”
Section: Introductionmentioning
confidence: 99%
“…, 29,39,40 which are hopeful to improve both the structural stability and the PLQY of OIMHs. 39,41,42 In addition, self-trapped excitons (STEs) usually formed in low-dimensional OIMHs, which could generate broadband emission even covering the entire visible spectrum. 43 Therefore, it is particularly important to develop lead-free low-dimensional OIMHs.…”
Section: Introductionmentioning
confidence: 99%
“…Organic–inorganic hybrid metal halide materials have attracted extensive attention as semiconductor materials with exceptional structure and adjustability of luminescent properties, including high absorption coefficient, high electron–phonon coupling coefficient, and high photoluminescence quantum yield (PLQY), which have a wide variety of optoelectronic applications, such as lasers, light-emitting diodes, thin-film transistors, etc. Lead-based metal halide hybrids are usually used to understand luminescent materials with their high PLQY and tunable optical properties. However, the lack of structural stability resisting long-term light, moisture, or high temperature and heavy metal lead toxicity to humans and the environment all limit its further real applications. To overcome these problems, it is indispensable to obtain environmentally friendly stable organic–inorganic hybrid metal halide materials. Generally, using other inorganic materials instead of toxic lead materials and lowering the structural dimension can greatly reduce the toxicity and improve the stability, respectively. For instance, Xia et al reported that the 0D hybrid material of (C 8 H 14 N 2 ) 2 SnBr 6 shows excellent photostability under 80 min of continuous ultraviolet light irradiation, and the integrated intensity remained above 90% of the initial stage .…”
mentioning
confidence: 99%
“…[32][33][34] However, the simultaneous occurrence of ICT and consequent production of deeper initial colors are usually viewed as the negative factors for facilitating PIET and photochromism. [35][36][37][38][39][40][41][42][43][44][45][46][47][48][49] Recently, we reported that ultrafast visible-light photochromic properties of two NDI-based coordination polymers (CPs) can be realized by virtue of their absorption in the visible light region, implying that PIET can be promoted by ICT to some extent, 50 which is contradictory to the previous consensus on the relationship between ICT and PIET. Therefore, it is vital for the development of a new strategy to solve the discrepancy and clarify the effect of ICT on PIET, which is beneficial for the construction of organic-inorganic hybrid systems with excellent photochromic properties.…”
Section: Introductionmentioning
confidence: 94%